Identification of Common and Subtype-Specific Mutated Sub-Pathways for a Cancer - Yan, Haidan; Deng, Xusheng; Chen, Haifeng; Cheng, Jun; He, Jun; Guan, Qingzhou; Li, Meifeng; Xie, Jiajing; Xia, Jie; Gu, Yunyan; Guo, Zheng (Frontiers in Genetics, 2019)
The heterogeneity of cancer is a big obstacle for cancer diagnosis and treatment. Therefore, prioritizing combinations of driver genes that mutate in most patients of a specific cancer type or a subtype of this cancer is a promising way to tackle this problem. Here, we developed an empirical algorithm, named PathMG, to identify common and subtype-specific mutated sub-pathways for a cancer. By analyzing mutation data of 408 samples (Lung-data1) for lung cancer, three sub-pathways each covering at least 90% of samples were identified as the common sub-pathways of lung cancer. These sub-pathways were enriched with mutated cancer genes and drug targets and were validated in two independent datasets (Lung-data2 and Lung-data3). Especially, applying PathMG to analyze two major subtypes of lung cancer, lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LSCC), we found and validated six LUAD-specific sub-pathways and seven LSCC-specific sub-pathways. Two LUAD-specific and three LSCC-specific sub-pathways were significantly associated with the prognosis of lung cancer. Similar analyses were done for colorectal cancer. Together, PathMG provides us a novel tool to identify potential common and subtype-specific sub-pathways for a cancer, which can provide evidences for subtype diagnoses and pathway-targeted treatments.